Nasal verbalization of the Kanayatn Dayak Language - Eusabinus Bunau (Universitas Syiah Kuala, 2022)
This research aims to study the feature of nasals in the Kanayatn Dayak language, spoken in West Kalimantan, Indonesia, and whether they are replacive or additive to particular initial phonemes of the root. The data were collected by recording and interviewing five informants of 45-55 years old native speakers of Kanayatn Dayak. Through the descriptive linguistics approach to describe the linguistic features of the nasals, this study revealed that the feature could be both replacive and additive, depending on the initial phoneme of the root word the nasals enter. These replacive and additive nasal verbalization processes function as class-maintaining and class-changing based on the root class to the nasals attached. As a replacive, the nasal verbalization process replaces the first phoneme of the root with nasals /m-/, /n-/, /ŋ-/, and nasal /ɲ-/. As additive verbalization, it is added to first phoneme of the root by employing allomorph /ma-/ and alternant /m-/, allomorph /am-/, allomorph /an-/ and alternant /n-/, and nasal /ŋ-/ and allomorph /ŋa-/. The replacive nasal verbalization makes the first phoneme of root covert. It is replaced with the replacive nasals. Then, the additive verbalization process maintains the first phoneme of the root staying overt. As a result, these additive nasals also create double homorganic-nasal oral consonants at the first phoneme of the verbs. The verbalization process involving additive allomorph only maintains the first phoneme of the root staying overt. In complex word formation, nasal verbalization creates active transitive and intransitive verbs.